Antigen-dependent Proliferation of CD4(+) CD25(+) Regulatory T Cells In Vivo - Walker, Lucy S.K. (The Rockefeller University Press, 2003)
The failure of CD25(+) regulatory T cells (T(regs)) to proliferate after T cell receptor (TCR) stimulation in vitro has lead to their classification as naturally anergic. Here we use T(regs) expressing a transgenic TCR to show that despite anergy in vitro, T(regs) proliferate in response to immunization in vivo. T(regs) also proliferate and accumulate locally in response to transgenically expressed tissue antigen whereas their CD25(−) counterparts are depleted at such sites. Collectively, these data suggest that the anergic state that characterizes CD25(+) T(regs) in vitro may not accurately reflect their responsiveness in vivo. These observations support a model in which T(reg) population dynamics are shaped by the local antigenic environment.